The rational politics of cultural nationalism: subnational movements of South Asia in comparative perspective - Mitra, Subrata Kumar (British journal of political science, 1995)
The recent politics of South Asia has been dominated by separatist movements that have waged violent struggles to assert their control over parts of existing national states. The precise moment of the outbreak of these movements is influenced by the perception of the geopolitical context by their leaders and the stability of the central state against which they rebel. But their main driving force originates from a shared belief in their unique and distinct cultural identity, which, in their eyes, justifies their right to an exclusive homeland. This article examines subnationalism in South Asia as a special case of of cultural nationalism. Subnationalism has long been an anomaly for both liberal and Marxist social theorists, who concede its existence but cannot explain it adequately. The analysis undertaken here moves beyond the sociological and historical accounts of the origins and evolution of subnationalism in South Asia by formulating a political explanation drawing on theories of rational choice and collective action. The article argues that (a) leaders of subnationalist movements draw on both sentiments and interests, and (b) the direction and pace of these movements are influenced by the political resources that they are able to mobilize. Though the case studies on which the article draws are mainly from South Asia, the model that underpins them is applicable to other cultural and temporal contexts as well. (British Journal of Political Science / AuD)
Keywords: Südasien